Extracorporeal membrane oxygenation during pregnancy and peripartal. An international retrospective multicenter study. (July 2023) - Malfertheiner, S Fill; Brodie, D; Burrell, A; Taccone, FS; Broman, LM; Shekar, K; Agerstrand, C L; Serra, A L; Fraser, J; Malfertheiner, MV
Introduction: Extracorporeal Membrane Oxygenation (ECMO) may be used in the setting of pregnancy or the peripartal period, however its utility has not been well-characterized. This study aims to give an overview on the prevalence of peripartel ECMO cases and further assess the indications and outcomes of ECMO in this setting across multiple centers and countries. Methods: A retrospective, multicenter, international cohort study of pregnant and peripartum ECMO cases was performed. Data were collected from six ECMO centers across three continents over a 10-year period. Results: A total of 60 pregnany/peripartal ECMO cases have been identified. Most frequent indications are acute respiratory distress syndrome ( n = 30) and pulmonary embolism ( n = 5). Veno-venous ECMO mode was applied more often (77%). ECMO treatment during pregnancy was performed in 17 cases. Maternal and fetal survival was high with 87% ( n = 52), respectively 73% ( n = 44). Conclusions: Various emergency scenarios during pregnancy and at time of delivery may require ECMO treatment. Peripartal mortality in a well-resourced setting is rare, however emergencies in the labor room occur and knowledge of available rescue therapy is essential to improve outcome. Obstetricians and obstetric anesthesiologists should be aware of the availability of ECMO resource at their hospital or region to ensure immediate contact when needed.